2017
DOI: 10.1186/s12885-017-3123-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid eradication of colon carcinoma by Clostridium perfringens Enterotoxin suicidal gene therapy

Abstract: BackgroundBacterial toxins have evolved to an effective therapeutic option for cancer therapy. The Clostridium perfringens enterotoxin (CPE) is a pore-forming toxin with selective cytotoxicity. The transmembrane tight junction proteins claudin-3 and -4 are known high affinity CPE receptors. Their expression is highly upregulated in human cancers, including breast, ovarian and colon carcinoma. CPE binding to claudins triggers membrane pore complex formation, which leads to rapid cell death. Previous studies dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 52 publications
3
37
0
1
Order By: Relevance
“…2 ). It was therefore proposed to use CPE for tumor diagnosis and therapy 46 – 50 . Previous experiments demonstrated that CPE by binding to a subset of claudins, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). It was therefore proposed to use CPE for tumor diagnosis and therapy 46 – 50 . Previous experiments demonstrated that CPE by binding to a subset of claudins, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…CPE is regarded as a therapeutic tool for epithelial malignant tumors by utilizing the damage of CLDN4 and CLDN3 [11,53,54]. The 50%-inhibitory concentration of CPE for colon cancer cell lines was between 50-100 ng/ml [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bacterial toxins are gaining interest in targeted cancer therapy (Table 3 (Tab. 3) ; References in Table 3: Foss, 2000[ 46 ]; Karpinski and Szkaradkiewicz, 2013[ 61 ]; Nair at al., 2014[ 80 ]; Pahle et al, 2017[ 153 ]; Patyar et al, 2010[ 155 ]; Yang et al, 2013[ 181 ]; Zahaf and Schmidt, 2017[ 183 ]). They are produced naturally as virulence factors by various strains of pathogenic bacteria.…”
Section: Sources Of Natural Productsmentioning
confidence: 99%